Historia de tango - Taller de cine UNL (Taller de cine UNL, 2021)
2003 / 12 minutos / DVCAM Con: Sergio Abbate, Juliana Ulla, Mariano Gariboldi, Milagros Alarcón, Florencia Russo, Antonella Fiorito, Laura Lastra, Mario Cuello, Ricardo Llusá, Diego Rinaldi, Mario Pascullo, Priscila Sandoval